Acute Respiratory Distress and Its Risk Factors among Neonates Admitted in a Tertiary Care Center of Western Nepal - Adhikari, Jyoti; Aryal, Sajju; Gupta, Veena (Journal of Nepalgunj Medical College, 2017)
Background: Neonatal period is defined as a period from birth to under 4 weeks (<28 days) of age. It is a highly vulnerable time for an infant, who is completing many of the physiologic adjustments required for extra uterine existence. The term Respiratory distress (RD) is used to indicate signs & symptoms of abnormal respiratory pattern. Methods: All neonates admitted in neonatal intensive care unit of Nepalgunj Medical College, Kohalpur with respiratory distress were included. Same number of age and sex matched controls without RD were selected. Results: The NICU based hospital incidence of RD was 9.1% with male: female ratio 1.4:1 The Most Common etiology was neonatal sepsis (51.6%), followed by hyaline membrane disease (17.8%), TTN (12.7%), meconium aspiration syndrome (6%), birth asphyxia (5.08%), tracheoesophageal fistula (2%) and pneumothorax (2%). Newborns with poor APGAR score requiring resuscitation were more likely to develop RD (p=0.025). Newborns with birth weight <2.5 kg and >4 kg were 2 times likely to develop RD as compared to control group (p<0.012). There was 7 times higher risk of developing MAS when a baby was born through thick MSL as compared to control group (P<0.022). Inadequate ANC visit significantly increased RD in newborns (p<0.001). Babies born to mother with PROM for more than 18 hours were 5.5 times likely to develop RD (p<0.001) whereas those born to mother who had any source of infection were about 6 times at risk of developing respiratory distress than control group (p=0.007). Conclusion: Certain measures that could be taken to reduce the number of RD are: 1. discouraging early marriage and teenage pregnancy. 2. Increasing awareness regarding temporary and permanent contraceptive measures. 3. Promoting education of girls. 4. Increasing coverage of ANC visit in rural areas and 5. formulating integrated plan and policies from the Government level.